Compact Band-Selective Power Divider Using One-Dimensional Metamaterial Structure. (6th December 2019) - Park, Soonwoo; Han, Heeje; Kim, Chanwoo; Bae, Jaemin; Cho, Youngki; Kim, Hongjoon
Abstract : A band-selective power divider is demonstrated for the first time. By replacing lumped element right-handed (RH) and left-handed (LH) transmission lines (TL) in a conventional Wilkinson power divider, it is possible to achieve both power division and filtering simultaneously. By utilizing the positive phase propagation property of an RHTL, which works as a low-pass filter, and the negative phase propagation property of an LHTL, which works as a high-pass filter, the band-selective quarter-wave sections required to construct a Wilkinson power divider are implemented. The fabricated circuit shows an insertion loss in the range 1.7 dB–2.5 dB in the passband, with the circuit dimensions of merely 12 mm by 10 mm.